NETWORK PLANNING OF THE TECHNOLOGICAL CHAIN FOR TIMBER LAND DEVELOPMENT - Rukomojnikov, Konstantin; Mokhirev, Aleksandr; Burgonutdinov, Albert; Kunickaya, Olga; Voronov, Roman; Grigorev, Igor (Journal of Applied Engineering Science, 2021)
Making managerial decisions when choosing a variant of the technological chain for logging is complicated by the variety of natural and climatic conditions. The climatic features of the periods affect the productivity of technological machines and the cost of implementation. This research suggests using network planning to determine the technological chain of timber land development. The purpose of the research is construction of multi-purpose network models for planning the technological chain of logging operations in various production conditions of forestry enterprises operation. These models are aimed at making it possible to conduct calculations to increase the efficiency of labour, materials, funds, equipment distribution with the maximum reduction in the cost of logged products. As a result of the analysis of possible options for technological chains, several network models for the implementation of logging technological processes have been built.